Philosophie der Lebensführung: Ethisches Denken zwischen Existenzphilosophie und Konstruktivismus - Weiland, René (transcript, 2016)
Existentialism questions the meaning of human life. For Constructivism, this question is already answered: yes, it is pointless; the reality of the individual is, in any case, the complete reality – there is no "objectivity". These two mindsets are so foreign to each other, yet so near in their radical subjectivity. René Willand considers this strange proximity by moving away from the category of internal-external difference as a shifting term through which both mind-sets bind themselves together, reconsidering it as an interface of everything systemic and as a bottleneck of our individuation. A book for philosophers and psychologists as well as resilience researchers.